As funções da responsabilidade civil: as indenizações pecuniárias e a adoção de outros meios reparatórios - Carvalho, Luís Fernando de Lima (2013)
The advancement of relations between men in the world today involved new analyzes of law. It became an indipensable measure to review institutes that for long centuries followed the initial format developed by the Romans. Among the reasons that required the review of contemporary legal systems, respect for human dignity is presented as the main one. In societies formed by humans, nobody respects the human being. Damage is caused daily, minute by minute, second by second. The result is a natural reaction of private law, as it serves to regulate the relations between men. In the field of private law was then the reanalysis of the civil liability. Occurring damages, this system should worry about restoring the previous situation of the offender and the victim. But the liability can not only serve to repair damages. It also has to punish those who practice them and also ensure that they will no longer occur. Therefore, the purposes of liability becomes compensation, punishment and prevention, or caution, depending on how damages to be avoided are seen. The liability has distinct functions: one directed exclusively to the victim and the to damage that was caused (reparative function); another directed to the offending agent, mainly the intensity of his guilt and punishment that should imposed to him (punitive function); and the last related to the prevention of damages that may occur in the future and, therefore, is independent of the occurrence of the damage. Taking this into consideration, the effective application of civil liability, ie the means of redress, can not be exhausted in just pecuniary compensation. Each function of liability should have its mean of redress. The scope of this work is the presentation of these other means of redress